Analisis Keberlangsungan Kolaborasi Pemerintahan Kota Surabaya dengan Liverpool Dalam Pengembangan SDM Melaui Pendidikan Inklusi Sebagai Manifestasi Dari Program SCI (Sister Cities International) 2022 - Yulia Rimapradesi; Mohammad Latief (Prodi Ilmu Administrasi Negara, 2023)
As perspectives in post-Cold War international relations changed, non-state players started to appear. From that point on, monitoring politics and security causes the state to start acting. However, during the present outbreak, politics and security were not major concerns, which had an impact on the state as an actor and reduced its importance as a major player in international affairs. Other actors, including people, international organizations, and multinational corporations, are now able to start having an impact on the country because of new challenges including the economy, human rights, ecology, and terrorism. Due to growing concerns about international relations, sub-state entities, such as states, cities, and provinces, are increasingly able to take part in international operations. In order to support education for inclusive schools in Surabaya in 2022, the Surabaya MoU collaboration process with St. Vincent School Liverpool will be examined for sustainability in this study. The research's conclusions show how the two cities' agreement to assist in the enhancement of quality education for their residents is still being implemented. This study intends to give a general picture of the ongoing partnership between Liverpool and the Surabaya city administration in 2022 regarding inclusive education for people with disabilities and assess the challenges that arise during the engagement.